Getting to Know Cek Sam: The Biography of a Saree Cassava Chips Trader - Septia Farah Ningsih; Abdul Azis; Husaini (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
This research is entitled “Getting to Know Cek Sam: The Biography of a Saree Cassava Chips Trader”. It aims to: (1) identify and explain the background of Cek Sam’s early life before becoming a Saree cassava chips trader; (2) examine the strategies she employed in indtroducing Saree cassava chips to the wider community; and (3) analyze her life after gaining widespread public recognition. This study applies a qualitative approach using a biographical historical method with descriptive analytical characteristics. Data were collcted through interviews, literature review, documentation. The analyzis followed the stategs of heuristics, verification, interpretation, and historiography. The results of this study indicate that (1) Cek Sam, whole real name is Samsinar, came from a modest family and was accustomed to hard work from an early age. In 1987, before becoming widely known, she worked as a street vendor selling boiled corn, boiled peanuts, and cassva chips carried in a basin and offered directly to small shops (keude) near a mosque. (2) Her strategy in introducing Saree cassava chips included maintaining consstent product quality., providing friendly customer service, choosing a strategis shop location, and developing product innovations through various falvors. (3) after gaining public recognition, her life changed significantly in economic and social aspects. She was not only a trader but also an inspiring female figure who created employment opportunities, especially for women in her community. After her passing, the business has been continued by her children, ensuring sustainability and preserving her values of hard work and perseverance.